Taxonomic and Functional Ant Diversity Along tropical, Subtropical, and Subalpine Elevational Transects in Southwest China - Fontanilla, Alyssa M. (Insects, 2019)
Although elevational gradients of biodiversity have long been the topic of scientific research, information on patterns of, and processes that shape insect community structure across elevation is still lacking. Addressing this gap requires the use of both taxonomic and functional approaches when studying diversity across elevational gradients. In this study, we examined taxonomic and functional alpha and beta diversity of ant assemblages sampled along tropical, subtropical, and subalpine elevational transects in Yunnan Province, southwest China. Species richness was used to quantify taxonomic alpha diversity, and two indices (FD and FRic) were calculated using morphological measurements to quantify functional alpha diversity. Taxonomic and functional beta diversity were partitioned into their turnover- and nestedness-resultant components. Though temperature and functional alpha diversity decreased linearly with increasing elevation, taxonomic alpha diversity showed a significant logarithmic decrease, with few species present at elevations greater than 3000 m a.s.l. The turnover-resultant component of taxonomic beta diversity increased with increasing elevational distance, while the nestedness-resultant component of functional beta diversity increased with increasing elevational distance in the subtropical transect. The observed patterns of taxonomic and functional diversity reflected ants’ thermophilic nature, implying functional adaptations (i.e., nested functional diversity) at higher elevations where environmental conditions were unfavorable.